Mitral valve prolapse in patients with coronary artery disease. Echocardiographic-angiographic correlation. - Raizada, V (1977)
Echocardiography was performed in 25 consecutive patients with angina pectoris and angiographically demonstrable coronary artery disease. Left ventricular echograms detected late or pansystolic mitral valve bowing suggesting of mitral valve proplapse in 6/25 (24%). Left ventricular angiography showed prolapse of the posterior mitral leaflet in 15/25 (60%), including 5 detected by echocardiography. Significant triple vessel coronary disease was present in 11 of 15 patients with prolapsed mitralvalve. In each of the latter a greater than 90 per cent obstructive lesion was noted in at least one coronary artery: right coronary artery, 9 subjects (82%); left circumflex coronary artery, 5 patients (33%); and left anterior descending coronary artery, 4 patients (27%). Of 15 subjects with angiographic evidence of mitral valve prolapse, 13 had left ventricular asynergy-inferior or inferoposterior in 8 subjects (62%) and anterior or anteroapical in 5 subjects (38%). Eleven subjects had vectorcardiographic evidence of transmural myocardial infarction-inferior or inferoposterior in 9 (82%) and anteroseptal in 2 (18%). A single subject with mitral valve prolapse had mild mitral regurgitation. It is concluded that: (1) coexisting prolapse of the posterior mitral valve leaflet and coronary artery disease is usually associated with triple vessel obstructive lesions, (2) severe right coronary disease, inferior left ventricular wall asynergy, and inferior myocardial infarction are important angiographic and vectorcardiographic correlates, and (3) echocardiography will detect such mitral valve prolapse in only one-third of affected cases.